A Revolução Federalista (1893-1895): o contexto platino, as redes, os discursos e os projetos políticos liberal-federalistas - Costa, Marcus Vinicius da (2006)
The changes that are being processed worldwide nowadays, globalization, formation of international state communities, as European Union, South Market, have fostered important changes in the knowledge during the last decades. Several social scientists, from several subjects, have been trying to review their concepts, having as a target to understand this new reality. Thinking about the current integration process, or the integrationist projects in vogue in Latin America, demands a new look over the continent history. It s indispensable to rethink the question round the national-states formation, the federalism, the revolutions, in short, to rethink the political history of Platinum Region. Accordingly, the objectives of this work were to understand: the fundaments in which the federalist-liberal elite speech, that commanded the Revolution from 1893-1895 were based on; the platinum political-historical context in the late century XIX, mainly in Argentina, Uruguay and Rio Grande do Sul; the webs formed by the opposition groups from Argentina (Radicals), from Uruguay (Blancos) and from Rio Grande do Sul (federalist-liberals); the speech as well as the political project built by the federalist-liberals from Rio Grande do Sul, lead by Gaspar Silveira Martins. The work has been based mainly on bibliographic survey and documents copied in this bibliography, and it had a theoretical basis that runs through the Political history, Cultural history, added of an interdisciplinary dialogue. The federalist-liberals have based their speech on the conceptions present in the authors linked to the Natural People Law and the Liberalism-enlightenment, appropriated through formal education in schools and universities and also informal, through reading of party newspapers, party meetings or in secret societies, such as the freemasonry. The political oppositional groups from RS, Uruguay and Argentina have experienced very similar realities and their projects also approached in many points: they had been excluded from the administrations, claimed for the collectivity autonomy for the minority, the states (RS), the provinces (Argentina) and the departments (Uruguay), inside the federal state, had the federalism as a flag. These groups formed, in the period from 1893-1895, solidarity webs, with the objective of strengthening themselves. The federalist-liberals have built a speech where they reassured their political identity, justified the revolution, and built a project for the State, articulated with the blancos Uruguayans and radical Argentinians, where they cogitated the separation of Rio Grande do Sul from the Brazilian federation and the constitution of a new federal Republic in extreme South America.